2020
DOI: 10.1186/s12912-020-0407-2
|View full text |Cite
|
Sign up to set email alerts
|

Caring behavior and associated factors among nurses working in Jimma University specialized hospital, Oromia, Southwest Ethiopia, 2019

Abstract: Background: Nursing care behavior and nurse's perception of effective care behavior is an act, conduct, and mannerism enacted by professional nurses that convey concern, safety, and attention to the patient. Behavior associated with caring has a paramount role in linking nursing interaction to the client in experiences but, the concept is ambiguous and elusive toward different scholars to reach on common understanding. Only a few studies have been done on the caring behavior and associated factors globally, an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
50
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(72 citation statements)
references
References 17 publications
18
50
3
1
Order By: Relevance
“…This study is in line with the results of several studies, which reported that nurse caring behavior is influenced by job satisfaction. 2,16,17 Other studies suggest that job satisfaction can improve the performance of nurses and the quality of patient care. 9,[18][19][20] In this study, the salary and reward nurses receive is known to have an impact on the nurses' behavior.…”
Section: Characteristics Of Respondentsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study is in line with the results of several studies, which reported that nurse caring behavior is influenced by job satisfaction. 2,16,17 Other studies suggest that job satisfaction can improve the performance of nurses and the quality of patient care. 9,[18][19][20] In this study, the salary and reward nurses receive is known to have an impact on the nurses' behavior.…”
Section: Characteristics Of Respondentsmentioning
confidence: 99%
“…1 Nurses as professionals are responsible for the provision of high quality nursing care for better patient outcomes and every effort is made through their caring behavior. 2 Furthermore, caring is an interpersonal process with a specific context characterized by excellent nursing skills, interpersonal responsiveness, and intimate relationships initiated by the nurse's need and openness to care, as well as professional maturity and willingness to nurture their moral foundation. 3 In general, nurses perform sufficient patient care, however they often less attentive to caring behavior aspects.…”
Section: Introductionmentioning
confidence: 99%
“…In Oramia Hospitals in Southwest Ethiopia, nurses cannot apply caring aspects well (30%), and 50% of patients stated the elements of concern inclined to the poor (Oluma & Abadiga, 2020). Most nurses from an Acute National Health Service Trust only apply the caring principle to expressive aspects, such as listening to patient complaints but without empathy, while the monitoring aspect is not carried out correctly (Chana, Kennedy, & Chessell, 2015;Oluma & Abadiga, 2020). The quality of nursing work life has also decreased, as much as 32.6% of nurses are paid a low rate of the salaried sector, and working hours are not suitable.…”
Section: Introductionmentioning
confidence: 99%
“…Caring is an action based on affection, skill, empathy, responsibility, sensitivity, and support. Rewards by patients are needed for nurses in their work environment as an acknowledgment (Chana et al, 2015;Loke and Lee, 2020;Oluma & Abadiga, 2020;Rawnak, 2020). Caring is needed to solve these problems (Viselita, Handiyani, & Pujasari, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, service quality, regardless of whether hospitals are university-based or not and they are administered by which institutions or organizations, needs to be evaluated [ 3 ]. Hospital service quality can lead to employee and patient satisfaction as well as loyalty in patients toward hospitals, and encourages them to recommend such healthcare centers to friends and acquaintances [ 4 , 5 ]. Consideration of quality can thus reduce costs in organizations, increase efficiency, and provide long-term stability [ 6 ].…”
Section: Introductionmentioning
confidence: 99%